Leveraging Community Health Worker Program to Improve Healthcare Access for Sickle Cell Disease in Georgia - Jeanette Nu'Man; Milford Greene (Georgia Southern University, 2020)
A five-year project, Access to Care was developed and implemented by the Sickle Cell Foundation of Georgia (SCFG) leveraging community resources and partnerships to increase access and improve the quality of healthcare and healthcare coordination in an adult sickle cell disease (SCD) population in underserved and rural areas of Georgia. The project is comprised of three phases: (Phase 1) the Community Health Worker Program - to improve the health outcomes of individuals living with SCD through healthcare coordination; (Phase 2) the CME-accredited Provider Training Program - to increase the knowledge of non-specialty providers in Georgia to increase provider capacity and confidence to provide care and treatment for individuals with sickle cell disease; and (3) Sickle Cell Clinic Days - specialty care provided by a hematologist in minimally resourced and underserved areas including Augusta, Columbus, Macon and Savannah and counties. Eight hundred and sixty-nine (869) individuals in 75 Georgia counties have received care coordination services with 113 placed in medical homes. Three hundred and sixty-eight (368) health care providers have participated in six face-to-face trainings and 30 have participated in two webinars. Partnerships include local sickle cell associations and support groups; local health departments; hospitals/Emergency Departments; local medical societies; local academic institutions; stakeholders; Georgia Department of Public Health; Global Blood Therapeutics; and Morehouse School of Medicine. With 8,427 residents living with SCD, Georgia has the nation's fourth largest SCD population in the nation with the second highest SCD incidence among black and/or African American births in the nation. Evaluation measures include process and output data monitoring, collection of observational data, i.e., participation and appointment tracking, and case management recording utilizing case management software; pre-and post-questionnaires to measure changes in knowledge, attitudes, skills covered in workshops and seminars.